1965
DOI: 10.1002/ar.1091520307
|View full text |Cite
|
Sign up to set email alerts
|

The hemo‐chorial mouse placenta

Abstract: The placental barrier of the mouse was examined by light and electron microscopy and found to be of the henio-chorial and not of the hemo-endothelial type, as had been previously suggested. The suspected immunological function of the trophoblast is briefly reviewed, and attention drawn to the recent reclassification of the shrew placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…4 a and b), or gene expression markers such as Igf2 (27,28). With the use of all three assays, it was found that in the pUPD12 junctional zone, ''glycogen'' cells are more abundant than normal at E13.5 and E15.5 (data not shown), and their dramatic -t3), the fetal capillary endothelium (fc), and its associated basement membrane (bm) in the normal feto-maternal interface (e) as shown previously (25,26). The outermost trophoblast layer (t3), which is cytotrophoblastic (25), is loosely attached to the middle layer (t2), which is syncytial (25).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…4 a and b), or gene expression markers such as Igf2 (27,28). With the use of all three assays, it was found that in the pUPD12 junctional zone, ''glycogen'' cells are more abundant than normal at E13.5 and E15.5 (data not shown), and their dramatic -t3), the fetal capillary endothelium (fc), and its associated basement membrane (bm) in the normal feto-maternal interface (e) as shown previously (25,26). The outermost trophoblast layer (t3), which is cytotrophoblastic (25), is loosely attached to the middle layer (t2), which is syncytial (25).…”
Section: Resultssupporting
confidence: 59%
“…The labyrinth is the zone where fetal blood and maternal blood circulate within fetal capillaries and maternal blood spaces, respectively, for physiological exchange through zygote-derived feto-maternal interfaces (1,2,(24)(25)(26). These labyrinthine interfaces consist of the endothelial cells of fetal capillaries, their associated basement membrane, and a trilaminar layer of trophoblast cells that directly lines the maternal blood spaces (25,26) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The placentas of monkeys, lambs, pigs, goats, rats, and mice have each been studied as models of human placental structure and function, but there are significant differences among their macro-and microstructures that must be considered (174,311,536,553,575,644).…”
Section: Placental Structure and Expression Of Calciotropic And Phospmentioning
confidence: 99%
“…B) HUMAN DATA. Human placentas are discoid and hemochorial and are considered to have similar structure, function, and diffusional characteristics to placentas of mice and rats (174,311,536,553). They are hemomonochorial, meaning that a single trophoblast cell layer separates maternal and fetal blood.…”
Section: Placental Structure and Expression Of Calciotropic And Phospmentioning
confidence: 99%
“…4L). The fetal vasculature in the labyrinth, which is separated by the trophoblast layers from maternal blood sinuses, undergoes rapid growth during placenta development (Kirby and Bradbury, 1965). Thus, while VEGFRY flk-1 expressing cells were in proximity of the VEGF producing cells, the VEGFRl/flt-1 expressing cells were located at a relatively high distance.…”
Section: Expression Of Vegfruflt-1 During Vasculogenesis and During Pmentioning
confidence: 99%